Sikap Politik Muhammadiyah terhadap Kebijakan Pemerintah Orde Baru 1968-1989 - Asmaul Fauziyah (Department of History and Islamic Civilization, Faculty of Adab and Humaniora, UIN Sunan Ampel Surabaya, 2019)
Abstract: The research in this article aims to determine the political attitude of Muhammadiyah during the New Order era. The problems that will be discussed in this thesis include, (1) How did Muhammadiyah perform during the New Order era in the fields of politics, socio-economics, and education. (2) What are the political, religious and educational policies of the New Order government. (3) What is Muhammadiyah's political attitude towards the policies of the New Order government in 1968-1989. The research method used in this thesis is a historical research method consisting of heuristic, verification, interpretation and historiography stages. The approach used is a historical approach that aims to examine, reveal or explain events that occurred in the past. Meanwhile, the theoretical basis used in this study is the theory of political behavior as defined by Ramlan Surbakti. The results of this study indicate that: (1) New Order Muhammadiyah's progress in the political field: efforts to rehabilitate Masjumi, form Parmusi, and let go of practical politics. Socio-economic field: community empowerment and Indonesia's economic development. Education sector: Through the Muhammadiyah education sector, there is massive vertical social mobility. (2) The New Order government issued policies against Muslims, namely in the political field: prohibition of Masjumi rehabilitation, intervention in Parmusi's leadership, party fusion and the Organizational and Social Bill. (3) Muhammadiyah shows an allocative political attitude in the form of suggestions, opinions and considerations through lobbying, gatherings and official letters to the government that are able to influence the government's policies. Keywords: Muhammadiyah, political attitude, government, policy, new order